The Influence of the Grammatical Agent on the Negation of Grammatical Rulings - Nibras Abdulkadhim Thani Tali, Researcher; Riyadh Abboud Ahwain, Professor Dr. (lark, 2026)
The present study aims to explore the impact of the agent in eliciting judgments of negation within Arabic grammar. It examines the grammatical structures rejected by grammarians, particularly within the classical Arabic heritage, who dismissed such constructions as deviations from the established foundations of Agency Theory.The issuance of a negation ruling was predicated on evidence and linguistic justifications derived by grammarians through the Agent Mechanism. It is essential to note that the concept of action is intrinsically linked to the speaker's articulation of the nominative, accusative, genitive, or jussive cases (Al-Mosuli, ). Thus, the Agent is defined as that which effects a change in another, be it nominative, accusative, genitive, or jussive, varying according to the specific nature of the Agents (Ibn Babshadh, 1978).The study explores the concept of negation from both linguistic and terminological perspectives. It subsequently elucidates a series of examples demonstrating the Agent's role in employing the judgment of negation. Furthermore, the study balances the views of those who negate a specific opinion against those who transmit such negations, ultimately weighing the evidence to favor what is proven correct through rigorous investigation. The study is concluded with a summary of the key findings.
Keywords: Agent, Negation, Grammar, Influence, Rejection of Ruling.